(untitled) (Comillas Journal of International Relations, 2016)
This chapter addresses Qatari-European Union (EU) relations from the perspective of current and future Qatari priorities and interests. In doing so, it examines Qatar’s evolving bilateral and region-to-region cooperation with Europe. It also analyzes recent trends in trade relations and the opportunities and constraints that Qatar faces in increasing gas exports to Europe. It examines how and why Qatar also greatly values Europe for the role that it plays in non-traditional areas of socio-economic cooperation including technology transfer, sustainable diversification, human capital development and investment (both overseas and inward). This article concludes by arguing that despite the Eurozone financial crisis and the Arab Spring, American dominance of the security sphere, and increased competition from Asia in the economic sphere, the EU and its constituent member states are important partners for Qatar. They are of particular importance to Qatar as key stakeholders in the country’s efforts to achieve socio-economic development through economic diversification.